Legal Study of Legal Treatment of Prisoners of War in the Perspective of Humanitarian Law: Legal Study of Legal Treatment of Prisoners of War in the Perspective of Humanitarian Law - Edwin; Tri Agus Suswantoro; Ahmad Jaeni; Tiarsen Buaton (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Enforcement prisoner wars waged onevery country are inseparable from provisions ofhumanitarian law. Every country involved in theorigination convention subject to the established ruleseven has been implemented well. Aims: From thebackground that has been described above, then writerinterested in raising this material in the creation of ajournal with the title "Treatment Against Prisoners ofWar Under Humanitarian Law”. Method: researchmethod used is the method study Library Research is aseries of activities related to methods library datacollection, reading and taking notes as well asprocessing research materials that utilize source library.As well as Internet Searching which is a technique datacollection through the assistance of technology in theform of tool or machine internet search where allinformation such as writing, data, pictures and so onfrom various eras available inside it. Result: A prisonerwar entitled on treatment as a prisoner war When thestatus as prisoner war Already fulfilled. Treatment toprisoner war has set up in terms and conditions lawhumanitarian. Provisions of Humanitarian Law the setup in Convention Geneva III 1949 on treatment toprisoner war. Conclusion: Violation law carried out byprisoners war must still processed in accordanceapplicable law However during the legal process walk aprisoner war must still get right his as prisoner war withthe provisions that have been set, then from That everycountry must own copy convention geneva the sentenceinside it convention mentioned understood by a personprisoner war.